UK corporate capital structure and zombies: an econometric analysis - Javaheriafif, Sadegh (2017)
This Thesis examines the determinants of corporate capital structure during a period characterised by significant changes in the overall economic conditions. Empirical studies of capital structure generally concentrate on identifying the firm-specific factors that managers should consider in making capital structure decisions, while ignoring the possible implications of the overall economic conditions that could affect the firms’ financing decisions. Given that the 2007 Global Financial Crisis (GFC) was accompanied by an economic recession, this provides a unique opportunity to investigate the impact of the overall economic conditions on firm’s capital structure.